2013
DOI: 10.3329/bja.v9i2.15275
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Shape of the Coronoid Process in the Adult Human Mandible

Abstract: DOI: http://dx.doi.org/10.3329/bja.v9i2.15275 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.75-78

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The present study suggested that hooked shape was most commonly observed accounting for 59% of the total number of CPs, which was in accordance with the North Indian, West Indian, Northwestern Turkish and Bangladeshi population groups 11 , 22 24 . The triangular shape had a higher frequency in Southern Indian and Nepalese population 4 , 14 , whereas another study conducted in Western Turkish region found round shape to be more prevalent 5 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study suggested that hooked shape was most commonly observed accounting for 59% of the total number of CPs, which was in accordance with the North Indian, West Indian, Northwestern Turkish and Bangladeshi population groups 11 , 22 24 . The triangular shape had a higher frequency in Southern Indian and Nepalese population 4 , 14 , whereas another study conducted in Western Turkish region found round shape to be more prevalent 5 .…”
Section: Discussionsupporting
confidence: 86%
“…Until now, morphological characteristics of CP have been mainly described for different Asian and Turkish population groups 3 5 . To our knowledge, no study is available presenting such data in a pure Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
“…The variations in the shape of the coronoid process may serve as anthropological markers to evaluate various populations and races. The shape of the sigmoid notch is determined by the shape of the condylar process and the coronoid process [ 1 , 2 ]. Various legal and personal matters pertaining to an individual’s identity require the individual’s identification, including death certification.…”
Section: Introductionmentioning
confidence: 99%
“…We reported most common shape of coronoid process is triangular while round shape is least common, which is very much similar to findings of Issac B et al [5] , Khan TA et al [6] , Prajapati VP et al [3] , Nirmale et al [8] , Desai VC et al [9] , Sanmugam K. [11] & Kadam SD et al [12] . While Hossain SMA [7] & Mouna S et al [10] observed that hook shaped coronoid process was most commonly found. They reported triangular shaped coronoid process was second commonest type.…”
mentioning
confidence: 99%